Neurodevelopmental disorder associated with NARS1 gene mutation in a child with cerebral palsy - Nonkulovski, Danilo; Sulejmani, Haris; Memeti, Shaban (Medip Academy, 2024)
Cerebral palsy is the most common cause of chronic motor disability in children. CP has a multitude of causes, including developmental, genetic, metabolic, ischemic, infectious, and acquired, all of which result in comparable neurologic symptoms. As of right now, the cause of CP remains unclear. Research has found a substantial link between low birth weight, birth hypoxia, and poor fetal position and placenta. When diagnosing children with cerebral palsy and determining its cause, brain imaging is crucial. The final diagnosis should consider many factors, including physiological, topographic, ICF/functional, and neuroradiological categorization, origin, time of injury, concomitant disorders, sequelae, and nutritional status. This assists with planning, management, counseling, progress tracking, and prognosis. We present a case of a 5-year-old child with cerebral palsy who has a complicated clinical presentation including delayed psychomotor development, dysmorphia, and a verified pathogenic variation in the NARS1 gene linked to a neurodevelopmental condition. The child has been receiving frequent monitoring and multimodal therapies, such as physical therapy, defectologist sessions, and omega fatty acid supplements. Genetic testing found a pathogenic variant in the NARS1 gene, emphasizing the significance of genetic screening for parents to prevent recurrence in future pregnancies. Collaboration with special education instructors and speech therapists remains active to meet the child's communicative and cognitive requirements.
Keywords: Cerebral palsy; NARS1 gene mutation; Disability; Therapy